2004
DOI: 10.1590/s0100-41582004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Histopatologia da interação Alternaria solani e tomateiros resistente e suscetível

Abstract: Para esclarecer a natureza da resistência à pinta-preta (Alternaria solani) em tomateiro resistente (Lycopersicon hirsutum var. glabratum) cv. CNPH 417 e suscetível (L. esculentum) cv. Miller, avaliou-se o processo de infecção, através da histopatologia. Às 6, 12, 24, 36, 48 e 72 h após as inoculações (h.a.i.) de suspensões de conídios, coletaram-se amostras de tecidos foliares que foram submetidas ao clareamento, à inclusão em resina para confecção de cortes semifinos e ao processamento para microscopia eletr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
3
12
0
2
Order By: Relevance
“…The absence of apparent orientation of the germ tubes on the leaf surfaces found in our work, was also reported by Araújo and Matsuoka (2004) Aveling and Venter (2003) in A. cassiae -Vigna unguiculata. In spite of the apparent random pattern in the growth of the germ tubes, the majority of the appressoria were formed at the junctions between the epidermal cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The absence of apparent orientation of the germ tubes on the leaf surfaces found in our work, was also reported by Araújo and Matsuoka (2004) Aveling and Venter (2003) in A. cassiae -Vigna unguiculata. In spite of the apparent random pattern in the growth of the germ tubes, the majority of the appressoria were formed at the junctions between the epidermal cells.…”
Section: Discussionsupporting
confidence: 92%
“…In spite of the apparent random pattern in the growth of the germ tubes, the majority of the appressoria were formed at the junctions between the epidermal cells. This has been observed by some authors in A. solani (ARAÚJO; MATSUOKA, 2004;DITA et al, 2007) and in other Alternaria species (AVELING; SNYMAN; RIJKENBERG, 1994;McROBERTS;LENNARD, 1996;BOEDO et al, 2008) infecting a variety of hosts. Hancock and Huisman (1981) suggested that the general features of leaf topography and fluctuations in the nutrient microclimate around the cell junctions could stimulate the formation of appresoria at these sites.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Albuq. ); tomato (Alternaria solani Sorauer); and soybean (P. pachyrhizi) (Bentes & Matsuoka, 2002;Araujo & Matsuoka, 2004;Magnani et al, 2007). The results of this study indicate that different genotypes of gladiolus grown FIGURE 2 -Percentages of appressorium formation of Curvularia gladioli inoculated on the lower surface of leaves of Gladiolus calliantus and Gladiolus grandiflorus vars.…”
mentioning
confidence: 80%